Stable isotope and fatty acid analysis reveal the ability of sea cucumbers to use fish farm waste in integrated multi-trophic aquaculture. (15th September 2022) - Cutajar, Karl; Falconer, Lynne; Massa-Gallucci, Alexia; Cox, Rachel E.; Schenke, Lena; Bardócz, Tamás; Andolina, Cristina; Signa, Geraldina; Vizzini, Salvatrice; Sprague, Matthew; Telfer, Trevor C.
Abstract: Stable isotope ratios, carbon (δ 13 C) and nitrogen (δ 15 N), and fatty acids validated the trophic connection between farmed fish in a commercial nearshore fish farm and sea cucumbers in the Mediterranean Sea. This dual tracer approach evaluated organic matter transfer in integrated multi-trophic aquaculture (IMTA) and the ability of sea cucumbers to incorporate fish farm waste (fish faeces and uneaten artificial fish feed) into their tissue. Between October 2018 and September 2019, Holothuria (Roweothuria) poli Delle Chiaje, 1824, co-cultured at IMTA sites directly below one of the commercial fish cage, at 10 m and 25 m from the selected fish cage, and at two reference sites over 800 m from the fish farm. Sea cucumbers were sampled from each site in February, May and September, except at 0 m due to mass mortalities recorded here in the first month of study. Isotopic mixing models revealed that fish farm organic waste was the dominant dietary source for H. poli in IMTA at 10 m and 25 m from the cage. The contribution of marine plant-derived organic matter, Posidonia oceanica leaves and rhizomes, was least important. The isotopic signatures of sea cucumber tissues at reference sites were not explained by the sampled food resources. Importantly, fatty acid profiling revealed a high abundance of individual terrestrial plant fatty acids, such as oleic (18:1 n -9), linoleic (18:2 n -6) and eicosenoic (20:1 n -9) acids in sea cucumber tissue at 10 m and 25 m from the fish cage, presumably linked to the terrestrial plant oil content of the fish feeds. At the reference sites, sea cucumber tissues were characterised by higher relative abundance of arachidonic acid (20:4 n- 6) acid, and the natural marine-based eicosapentaenoic (20:5 n -3) and docosahexaenoic (22:6 n -3) acids. These analyses revealed important differences in the composition of H. poli between the IMTA and reference locations, driven by aquaculture-derived waste near fish cages. Moreover, this study revealed temporal variation in food availability and quality, and possible differences in the physiological responses of H. poli . Stable isotope analysis and fatty acid profiling provided complementary evidence for the important dietary preferences of H. poli and validated the potential of sea cucumbers to uptake aquaculture organic waste as part of inshore fish–sea cucumber IMTA. It reveals the important implications that an established trophic link has on the viability of using sea cucumbers for the development of IMTA and the sustainable expansion of aquaculture. Highlights: Dual tracers used to assess organic matter flow in integrated multi-trophic aquaculture. Stable isotope and fatty acid analysis show sea cucumbers use fish farm organic wastes. Aquaculture-derived organic waste was the dominant food for co-cultured sea cucumbers. Sea cucumber diet reflects spatial and temporal variation in food availability and quality.